2020
DOI: 10.21203/rs.2.21568/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between Aminotransferase/alanine Aminotransferase Ratio and Cardiovascular Disease mortality in Patients on Peritoneal Dialysis

Abstract: Background: Elevated aspartate aminotransferase/alanine aminotransferase (AST/ALT) ratio is an independent risk factor for cardiovascular disease (CVD) among the general population. However, an association between AST/ALT ratio and CVD mortality in patients on peritoneal dialysis (PD) has received little attention.Methods: A total of 2224 incident PD patients from multi-centers were enrolled from November 1, 2005, to June 30, 2017, in this retrospective cohort study. The primary endpoint was CVD mortality. Eli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Variables for adjustment were carefully chosen, given the number of events available, clinical importance, and published studies. [16][17][18] Three models were conducted: model 1, with no adjustment; model 2, with adjusting for age and sex; and model 3, with adjusting for other confounding factors based on model 2. In addition, we also performed smooth curve fitting (penalized spline method) and subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variables for adjustment were carefully chosen, given the number of events available, clinical importance, and published studies. [16][17][18] Three models were conducted: model 1, with no adjustment; model 2, with adjusting for age and sex; and model 3, with adjusting for other confounding factors based on model 2. In addition, we also performed smooth curve fitting (penalized spline method) and subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a longitudinal cohort study [16] included 3494 Japanese community-checked subjects that showed a high AST/ALT ratio (>90%) was an independent predictor of all-cause and cardiovascular mortality. Feng et al [17] performed a multicenter retrospective study which consisted of 1579 patients on peritoneal dialysis. It reported that a higher AST/ALT ratio was independently associated with an increased risk of CVD mortality compared with their counterparts (HR = 1.43, 95% CI:1.08–1.41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation